Consumers’ Intention to Purchase Green Skincare Products: Evidence from China - Rahman, Md. Jahidur; Lao, Keye; Biswas, Shyamapada; Sultana, Rakiba; Kennedyd, Sarmann I. (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study examines factors affecting customers’ intention to purchase green skincare products in China to provide some managerial recommendations to existing companies. The theory of planned behavior was applied to formulate our research hypotheses and establish our proposed model. A total of 121 Chinese consumers responded to a survey we conducted online. Process and structural equation modeling are also employed to test the moderation effect (Hayes & Preacher, 2013). We find that consumers’ attitudes, subjective norms, and perceived behavior control significantly affect their purchase intention. Moreover, the country of origin and price sensitivity has a moderation effect on the above relationships. The above findings can help green skincare companies to understand customer purchase behaviors in these modern times. This study contributes to the literature by addressing the gap in previous research on green skincare products in Mainland China. The respondents comprise Chinese university students who will become the main customers in the next few years. This study provides novel findings and inspires skincare companies to increase customer purchase intention by changing their strategy based on its influencing factors.